The relationship between inter-pregnancy interval and gestational age with labor complications at the Sele Be Solu Regional Public Hospital of Sorong City, West Papua - Fegita Beatrix Pajala; Erfen Gustiawan Suwangto; Yunisa Astiarani; Astrid Fransisca Padang (Universitas Udayana, 2020)
Background and purpose: Labor complications are conditionsduring or after labor that can threaten life of the mother and the baby to be born. Some factors have been associated with labor complications, including inter pregnancy interval and gestational age. This study was conducted to determine the relationship between inter pregnancy interval and gestational age with labor complications at the Sele Be Solu Regional Public Hospital of Sorong City. Methods: This study was an analytic observational study with a cross-sectional design. The samples of this study were pregnant women who gave birth at the Sele Be Solu Regional Public Hospitalof Sorong City in 2016-2018 and met the inclusion criteria. We used secondary data from the medical records retrieved in July to August 2019. We retrieved mothers’ identities (age, education, employment status), inter-pregnancy interval, gestational age and labor complications. A number of 261 samples (121 with labor complications and 140 without labor complications) were selected using convenience sampling technique. Descriptive analysis and Chi-Square test with SPSS 25.0 were performed. Results: Most of the mothers (85.8%) were in the non-high-risk age group, graduated from senior high school or above (82%), were not employed/housewives (68.6%), the majority (67.8%) of inter-pregnancy interval was in the non-high-risk group, more than half (52.5%) of gestational age was in the high-risk group and the most common type of complications (17.2%) was the premature rupture of membranes. There were significant relationship between age (p<0.001; OR=5.201; 95%CI: 2.275-11.889), inter-pregnancy interval (p<0.001; OR=2.955; 95%CI: 1.722 5.070) and gestational age (p<0.001; OR=4.606; 95%CI: 2.722-7.794) with labor complications. There were no relationship between education (p=0.166; OR=0.599; 95%CI: 0.312-1.151) and employment status (p=0.230; OR=1.428; 95%CI: 0.845-2.412) with labor complications. Conclusions: There are significant relationship between inter-pregnancy interval and gestational age with labor complications. Health offices and health workers have an essential role in minimizing the risk of labor complications by providing early detection of possible labor complications and active counseling to the community especially women of childbearing age.